1977
DOI: 10.1136/bmj.1.6066.943
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast and Crohn's disease.

Abstract: SummaryThe breakfast habits in adult life of 34 patients with Crohn's disease were compared with those of 68 matched controls. Cornflakes were being eaten at least weekly by 23 of the patients (67 6%) at the time that their symptoms began, compared with 17 (25%) of the controls at the corresponding time. Only one of the 34 patients had not eaten cornflakes at all, compared with half of the controls. A significant but weaker association was found between Crohn's disease and the eating of wheat cereals. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1979
1979
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(16 citation statements)
references
References 3 publications
1
15
0
Order By: Relevance
“…6, 7). Another difference which has been reported is a high intake of breakfast cereals, especially cornflakes (3). although Ar cher and Harvey (2) and Rawcliffe and Truelove (8) were unable to confirm this.…”
mentioning
confidence: 53%
“…6, 7). Another difference which has been reported is a high intake of breakfast cereals, especially cornflakes (3). although Ar cher and Harvey (2) and Rawcliffe and Truelove (8) were unable to confirm this.…”
mentioning
confidence: 53%
“…The nature of such causative factors remains a matter for speculation and current suggestions include transmissible infective agents (Mitchell and Rees, 1970), viruses (Whorwell et al, 1977), poorly encapsulated mycobacteria (Burnham et al, 1978), and diet (Martini and Brandes, 1976;James, 1977;Mayberry et al, 1978). There appears to be a small overall preponderance of the disease in women with a rate of 1:1V4.…”
Section: Discussionmentioning
confidence: 99%
“…Tursi et al [99] provided data to show a high prevalence of celiac disease among patients affected by CD, and indeed suggested that all CD patients should be started immediately on a glutenfree diet at diagnosis. James [100] showed the extent to which certain breakfast cereals, including wheatbased cereals, increased the probability of CD. These overlaps between celiac disease and CD could well relate to the HLA genotypes, although that question has not been formally investigated at this time.…”
Section: Mhcii and Hlamentioning
confidence: 99%